Improving Immunotherapy Efficacy in Soft-Tissue Sarcomas: A Biomarker Driven and Histotype Tailored Review - Roulleaux Dugage, Matthieu; Nassif, Elise F.; Italiano, Antoine; Bahleda, Rastislav (Frontiers in Immunology, 2021)
Anti-PD-(L)1 therapies yield a disappointing response rate of 15% across soft-tissue sarcomas, even if some subtypes benefit more than others. The proportions of TAMs and TILs in their tumor microenvironment are variable, and this heterogeneity correlates to histotype. Tumors with a richer CD8+ T cell, M1 macrophage, and CD20+ cells infiltrate have a better prognosis than those infiltrated by M0/M2 macrophages and a high immune checkpoint protein expression. PD-L1 and CD8+ infiltrate seems correlated to response to immune checkpoint blockade (ICB), but tertiary lymphoid structures have the best predictive value and have been validated prospectively. Trials for combination therapies are ongoing and focus on the association of ICB with chemotherapy, achieving encouraging resutls especially with pembrolizumab and doxorubicin at an early stage, or ICB with antiangiogenics. There is also a synergy ith oncolytic viruses and intratumoral talimogene laherpavec yields an impressive 35% ORR when associated to pembrolizumab. Adoptive cellular therapies are also of great interest in tumors with a high expression of CTAs, such as synovial sarcomas or myxoid round cell liposarcomas, and an ORR ranging from 20 to 50%. It seems crucial to adapt the design of clinical trials to histology. Leiomyosarcomas are characterized by complex genomics but are poorly infiltrated by immune cells and do not benefit from ICB. They sould be tested with PIK3CA/AKT inhibition, IDO blockade, or treatments aiming at increasing antigenicity (radiotherapy, PARP inhibitors). DDLPS are more infiltrated and have higher PD-L1 expression, but responses to ICB remain rare. They should be combined with MDM2 antagonists or anti-CDK4/6 therapies. UPS harbor the highest CNA and mutation rate, and a rich immune infiltrate with TLS. They have a promising 15-40% ORR to ICB. Trials for ICB should focus on immune-high UPS. Association of ICB with FGFR inhibitors is promising in the immune-low group of UPS. Finally translocation-related sarcomas are heterogeneous, and although synovial sarcomas is poorly infiltrated and have a poor response rate to ICB, ASPS largely benefit from ICB monotherapy or its association with antiangiogenics agents. Targeting specific neoantigens through vaccine or adoptive cellular therapies is probably the most promising approach in synovial sarcomas.